Legal Protection of Copyright in the Digital Era - Alsamara, Tareck; Iriqat, Mohammed; Zamouna, Almokhtar (Journal of Ecohumanism, 2025)
Copyright right is a term that denotes the privileges given to creators of various types of works, regardless of their genre, quality or destination. Copyright law recognizes the right of an author based on his personal creation. It consists of a monopoly of exploitation for the author's lifetime and an additional 70 years following their death to his successors. Now that the majority of content is in digital format and is globally accessible, the necessity to protect author’s interests has grown over the last decade. However, the development of the Internet has considerably complicated the protection of copyright. Digital technology facilitates infringements (copies, illegal downloading, etc.), which is prompting countries to develop and implement more effectives way to fight against digital piracy. This article will explore the challenges of copyright protection in the Internet and describe some of the mechanisms to used protect copyright in the electronic environment.